2020
DOI: 10.1186/s12884-020-02978-w
|View full text |Cite
|
Sign up to set email alerts
|

Promoting positive maternal, newborn, and child health behaviors through a group-based health education and microfinance program: a prospective matched cohort study in western Kenya

Abstract: Background: Chamas for Change (Chamas) is a group-based health education and microfinance program for pregnant and postpartum women that aims to address inequities contributing to high rates of maternal and infant mortality in rural western Kenya. In this prospective matched cohort study, we evaluated the association between Chamas participation and facility-based delivery. We additionally explored the effect of participation on promoting other positive maternal, newborn and child health (MNCH) behaviors. Meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…Our findings strengthen evidence from an earlier Chamas pilot that similarly demonstrated increased odds of achieving these outcomes compared with the standard of care in rural western Kenya. 15 Collectively, these findings highlight our intervention's potential to improve MNCH outcomes by leveraging existing community health resources and infrastructure in settings like Kenya. This work has several limitations.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Our findings strengthen evidence from an earlier Chamas pilot that similarly demonstrated increased odds of achieving these outcomes compared with the standard of care in rural western Kenya. 15 Collectively, these findings highlight our intervention's potential to improve MNCH outcomes by leveraging existing community health resources and infrastructure in settings like Kenya. This work has several limitations.…”
Section: Discussionmentioning
confidence: 86%
“…Intervention clusters participated in the Chamas programme (programme details are published elsewhere). 15 Briefly, Chamas is a group-based, CHV-led health education programme that supports women during the first 1000 days of their child’s life. Women randomised to the intervention arm participated in Chamas in lieu of receiving individual home visits (standard of care).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A pilot study evaluating the first year of this program demonstrated significant associations between participation and the likelihood of practicing positive MNCH behaviors, including attending adequate antenatal care and exclusively breastfeeding. 14,15 To test our hypothesis that maternal participation in Chamas improved MNCH outcomes, including ECD, we conducted a cluster-randomized controlled trial in Trans Nzoia County, Kenya. In this article, we report results from developmental screening questionnaires (DSQ) completed on children born during the trial at 1-year follow-up.…”
Section: Introductionmentioning
confidence: 99%